Penyuluhan Fisioterapi K3 dan Ergonomi Meningkatkan Pemahaman Pegawai Bengkel B-Garage Batu Tentang Pencegahan Nyeri Leher dan Punggung Bawah - Halief Rahmadillah Akbar; Nikmatur Rosidah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Work activities in workshops often require static and repetitive body positions, such as bending over, lifting heavy loads, or reaching into narrow areas of vehicles. These habits can gradually cause muscle tension and lead to neck and lower back pain. Given the high risk, physiotherapy counseling on occupational safety and health (OSH) and ergonomics was conducted to provide practical understanding to B-Garage, Batu City workshop workers. The counseling was delivered interactively through material presentations, direct discussions, and demonstrations of stretching exercises that can be easily applied in daily activities. The results of the activity showed a very significant increase in knowledge; participants who initially did not understand the principles of ergonomics and musculoskeletal pain prevention were able to identify work risks and practice stretching exercises correctly after the education session. This change was clearly evident from the post-test results, which showed a significant overall improvement compared to the pre-test. These findings indicate that physical therapy education not only enhances knowledge but also promotes behavioral changes toward safer, more comfortable, and more productive work patterns.